2018
DOI: 10.1111/sltb.12461
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality Disclosed Online: Using a Simulated Facebook Task to Identify Predictors of Support Giving to Friends at Risk of Self‐harm

Abstract: Although peer support in response to online disclosures of suicidality may be imperative for suicide prevention efforts, little is known as to how often support is provided or what predicts giving support. This study addresses this issue by investigating the odds of providing peer support in response to simulated online disclosures of suicidality. While interacting with a simulated Facebook newsfeed, participants (N = 690, M = 20.24, 527 female) were given the opportunity to leave comments on two posts disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The majority of the included studies were descriptive in nature; exploring the nature of the content found online (51 studies), describing user knowledge (2 studies) or exploring user experiences (28 studies). There were only six experimental studies (An and Lee, 2019; Cheng and Yom-Tov, 2019; Corbitt-Hall et al , 2016; Corbitt-Hall et al , 2019; Lewis et al , 2018; Till et al , 2017). Only four of the included studies had a longitudinal element (Arendt et al , 2019; Cheng and Yom-Tov, 2019; Scherr and Reinemann, 2016; Till et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the included studies were descriptive in nature; exploring the nature of the content found online (51 studies), describing user knowledge (2 studies) or exploring user experiences (28 studies). There were only six experimental studies (An and Lee, 2019; Cheng and Yom-Tov, 2019; Corbitt-Hall et al , 2016; Corbitt-Hall et al , 2019; Lewis et al , 2018; Till et al , 2017). Only four of the included studies had a longitudinal element (Arendt et al , 2019; Cheng and Yom-Tov, 2019; Scherr and Reinemann, 2016; Till et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, in Tandon’s RCT (Tandon et al, 2018) the perception of social support outperformed cognitive restructuring as a mediator in the preventive effect of post-partum depression of the ‘Mothers and Babies’ intervention. Another aspect to approach in future research are social support interventions based on ICTs, that is, via apps (Rigabert et al, 2020) and the use of electronic social networks, that is, Facebook (Corbitt-Hall et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are concerns that certain types of content (eg, graphic information or images) may cause distress, lead to imitative suicidal behavior, and have been thought to contribute to suicide clusters [ 6 ]. In addition, young people may be exposed to expressions of suicide risk posted by others but feel ill-equipped to respond [ 7 ].…”
Section: Introductionmentioning
confidence: 99%